Arterial compliance probe for cuffless evaluation of carotid pulse pressure - Joseph, Jayaraj; P M, Nabeel; Shah, Malay Ilesh; Sivaprakasam, Mohanasankar (PloS one, 2018)
Assessment of local arterial properties has become increasingly important in cardiovascular research as well as in clinical domains. Vascular wall stiffness indices are related to local pulse pressure (ΔP) level, mechanical and geometrical characteristics of the arterial vessel. Non-invasive evaluation of local ΔP from the central arteries (aorta and carotid) is not straightforward in a non-specialist clinical setting. In this work, we present a method and system for real-time and beat-by-beat evaluation of local ΔP from superficial arteries-a non-invasive, cuffless and calibration-free technique. The proposed technique uses a bi-modal arterial compliance probe which consisted of two identical magnetic plethysmograph (MPG) sensors located at 23 mm distance apart and a single-element ultrasound transducer. Simultaneously measured local pulse wave velocity (PWV) and arterial dimensions were used in a mathematical model for calibration-free evaluation of local ΔP. The proposed approach was initially verified using an arterial flow phantom, with invasive pressure catheter as the reference device. The developed porotype device was validated on 22 normotensive human subjects (age = 24.5 ± 4 years). Two independent measurements of local ΔP from the carotid artery were made during physically relaxed and post-exercise condition. Phantom-based verification study yielded a correlation coefficient (r) of 0.93 (p < 0.001) for estimated ΔP versus reference brachial ΔP, with a non-significant bias and standard deviation of error equal to 1.11 mmHg and ±1.97 mmHg respectively. The ability of the developed system to acquire high-fidelity waveforms (dual MPG signals and ultrasound echoes from proximal and distal arterial walls) from the carotid artery was demonstrated by the in-vivo validation study. The group average beat-to-beat variation in measured carotid local PWV, arterial diameter parameters-distension and end-diastolic diameter, and local ΔP were 4.2%, 2.6%, 3.3%, and 10.2% respectively in physically relaxed condition. Consistent with the physiological phenomenon, local ΔP measured from the carotid artery of young populations was, on an average, 22 mmHg lower than the reference ΔP obtained from the brachial artery. Like the reference brachial blood pressure (BP) monitor, the developed prototype device reliably captured variations in carotid local ΔP induced by an external intervention. This technique could provide a direct measurement of local PWV, arterial dimensions, and a calibration-free estimate of beat-by-beat local ΔP. It can be potentially extended for calibration-free cuffless BP measurement and non-invasive characterization of central arteries with locally estimated biomechanical properties.